Benchmarks for emissions trading: General principles for emissions scope - Vera Zipperer; Misato Sato; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Greenhouse gas emission benchmarks are widely implemented as a policy tool, as more countries move to implement carbon pricing mechanisms for industrial emissions. In particular, benchmarks are used to determine the level of free allowance allocation in emission trading schemes, which are distributed as a measure to prevent carbon leakage. This paper analyses how benchmark designs impact firms' production and business model decisions, particularly focusing on the coverage of direct and indirect emissions in the benchmark scope. We develop an analytical model and use the example of a steel mill to analyze and quantify how scope of indirect emissions coverage affect incentives. We seek to clarify generalized principles for efficient benchmark design, that provide a predictable policy framework for innovation and investment to decarbonize energy intensive industry.
Keywords: D04; H25; L51; L61; Q58; 330; Emissions Trading; Emission Benchmarking; Free allocation; Incentives; Low-Carbon Innovation